Australian Film Festivals Audience, Place, and Exhibition Culture - Stevens, Kirsten; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This is the first book to offer an in-depth examination of the history, operation, and growth of film festivals as a cultural phenomenon within Australia. Tracing the birth of film festivals in Australia in the 1950s through to their present abundance, it asks why film festivals have prospered as audience-driven spectacles throughout Australia, while never developing the same industry and market foci of their international fellows. Drawing on over sixty-years of archival records, festival commentary, interviews with festival insiders and ephemera, this book opens up a largely uncharted history of film culture activity in Australia. .
List of Illustrations -- List of Abbreviations -- Introduction -- 1.Enthusiastic Amateurs: Origins of Australia's film festival movement -- 2.Growth and Change: Curator-led festivals, fragmenting audiences and shifting film exhibition cultures -- 3. From Film Weeks to Festivals: The spread of the urban film festival after 1980 -- 4. Between Success and Failure: Crisis and recovery at the Melbourne International Film Festival -- 5. Programming Perceptions: Film festivals and the construction of taste -- 6. A Festival for Every Occasion: Niche programming, event culture and vertically integrated film festivals -- Conclusion -- Appendix 1: Early Melbourne and Sydney Film Festival programs -- Appendix 2: Summary of film exhibition and film culture activities, 1949-1990 -- Appendix 3: Film Festivals in Melbourne, 1949-2000 -- Appendix 4: Melbourne and Sydney Film Festivals -- Archives and Research Collections -- Bibliography.
Keywords: Australasian Cinema and TV; Australasian Culture